Efficacy and Safety Analysis of the New Aspheric Hydrophobic Acrylic Monofocal IOL Implantation at Short-Term Follow-Up - K. B. Pershin; N. F. Pashinova; A. Iu. Tsygankov; E. A. Korneeva (Oftalʹmologiâ)
Aim. To evaluate the results of implantation of a new hydrophobic acrylic monofocal IOL in an automated preloaded delivery system in the short-term follow-up period.Patients and methods. The prospective study included 89 patients (114 eyes) after bilateral or monolateral Clareon IOL implantation with a mean follow-up of 2.1 ± 0.4 (1–4) months. The age range was 53 to 87 (71.1 ± 5.2) years. A corneal incision of 1.8 mm was used in all cases. For implantation using the AutonoMe® system , the incision was enlarged by 0.2 mm for implantation IOL 26 D and higher. IOL optical power was calculated using the SRK/T formula; retrospective analysis was performed using the Hoffer Q, Haigis, Holladay II, Olsen, Barrett Universal II, and Kane formulas.Results. In all studied periods (1 day, 1 week and 1 month) there was statistically significant (p < 0.05) increase both of NCDVA (from 0.13 ± 0.02 in the preoperative period to 0.81 ± 0.07 in 1 month after surgical intervention), and BCDVA (from 0.32 ± 0.15 before surgery to 0.94 ± 0.11 after surgery). When assessing the percentage of eyes with an BCDVA of 0.9 or higher, a statistically significant (p < 0.05) difference was shown in all studied periods. The lowest MAE was shown for the Barrett Universal II (0.292), SRK/T (0.312) Kane (0.301), and Olsen (0.325) formulas. For the Hoffer Q and Holladay 2 formulas, MAE values were significantly higher (p < 0.05). The highest frequency of achieving the target refraction of ± 0.25 D was shown for the Barrett Universal II and Kane formulas (68 and 69 %, respectively), and the lowest for the Hoffer Q and Holladay 2 formulas (28 and 35 %, respectively). The primary endpoint of the study (BCDVA = 1.0) was achieved in 95.6 % (n = 109), with a deviation in BCVA of ± 0.1 noted in 4 eyes (3.5 %). No glistening was detected in the follow-up period up to 4 months.Conclusion. The paper presents an analysis of the first experience with the implantation of new Clareon monofocal IOLs in Russian Federation. The results of implantation of a new hydrophobic acrylic monofocal IOL in an automated preloaded delivery system showed a good clinical and functional effect, a high frequency of achieving the target result and the absence of significant side effects. The Kane, Barrett Universal II, and SRK/T formulas, using the Verion diagnostic navigation system, are recommended for calculating the optical power of the new IOL.